A high-resolution electric vehicle charging transaction dataset with multidimensional features in China - Yuanshi Zhang; Tongxin Xu; Tao Chen; Qinran Hu; Hongrui Chen; Xukun Hu; Zilv Jiang (Scientific Data)
Abstract The charging transaction data of electric vehicle (EV) users is crucial for studying charging market dynamics and formulating effective policies. However, due to factors such as the privacy of EV users and the complex coupling relationships between charging dealers, existing EV charging transaction datasets are plagued by issues such as incompleteness, significant bias, and a lack of real-time information. To address these issues, a real-time charging transaction dataset has been created, comprising 441,077 charging transactions collected from 13 charging stations in China over a 2-year period. The dataset includes detailed data of EV user charging transaction time, price and charging status, as well as the charging termination reasons and weather data for each charging session. This dataset offers references for identifying EV user behaviors and extracting charging fault factors from multiple aspects, supporting research applications in EV charging facility planning, EV charging and discharging management, and charging economic evaluation.